IMPLIKASI STRUKTUR MODAL, KEPEMILIKAN MANAJERIAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2019 - Oktarias Fatmawati; Gendro Wiyono; Agus Dwi Cahya (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to determine the implications of the variable capital structure, managerial ownership, and dividend policy on firm value in the property and real estate sub sector listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. The sample in this research is property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period with a total of 6 companies obtained using the purposive sampling method. The data analysis technique uses multiple linear regression analysis which is supported by classical assumption tests such as normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of this study indicate that capital structure has a positive and significant effect on firm value, managerial ownership has a positive and significant effect on firm value, while dividend policy has no significant effect on firm value. Simultaneously, capital structure, managerial ownership, and dividend policy have a positive and significant effect on firm value. Keywords: Capital Structure, Managerial Ownership, Dividend Policy dan Firm Value